STUDY OF WRITING PRODUCTION MATERIAL THROUGH TEXTUAL GENRES - Cleide Inês Wittke (Signum: Estudos da Linguagem, 2016)
A great number of studies about the process of language teaching and learning have focused on the analyses of didactic materials. Even though the didactic material itself does not guarantee successful learning, it can be seen as the first step towards this aim. Taken this into account and based on a socio-discursive interactionism approach to language, this article analyses the “Portuguese Language Olympics – Writing the Future”(“Olímpiada de Língua Portuguesa – Escrevendo o Futuro”)pedagogic material, in particular the sequences that make up the “Points of View “ (“Pontos de Vista”) volume, in order to investigate whether its didactic activitiesand exercises are in line with good practices of writing production, especially considering that the pedagogic material claims to work with textual genres. After contextualizing historically and theoretically the material under study, the didactic sequences in which argumentative essays are dealt with are analyzed in order to look for textual, linguistic, discursive and enunciative elements that can define and characterize the writing project.